2021
DOI: 10.3892/mmr.2021.11950
|View full text |Cite
|
Sign up to set email alerts
|

circRNA‑0006896‑miR1264‑DNMT1 axis plays an important role in carotid plaque destabilization by regulating the behavior of endothelial cells in atherosclerosis

Abstract: Atherosclerosis (AS) is a chronic inflammatory disease of the vascular wall with multiple causes. AS is the primary pathological basis of cardiovascular disease and stroke. Moreover, carotid plaque rupture and thrombus formation are the main causes of ischemic stroke. Therefore, understanding the formation of carotid plaques may help improve the prediction and prevention of cardiovascular and cerebrovascular events. Endothelial cell dysfunction results in re-endothelialization and angiogenesis in atherosclerot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…A few studies have found an association between exosomal circRNAs and the pathogenesis of AS. 444 , 445 Wen et al suggested that the expression of exosomal circRNA‑0006896 in circulation is positively associated with the levels of TG, LDL, and C-reactive protein (CRP) in patients with unstable plaque atherosclerosis. 445 The study also reported that the elevated circulating exosomal circRNA‑0006896 leads to high expression of circRNA‑0006896 in ECs, which results in an increases in capacities of proliferation and migration in ECs.…”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies have found an association between exosomal circRNAs and the pathogenesis of AS. 444 , 445 Wen et al suggested that the expression of exosomal circRNA‑0006896 in circulation is positively associated with the levels of TG, LDL, and C-reactive protein (CRP) in patients with unstable plaque atherosclerosis. 445 The study also reported that the elevated circulating exosomal circRNA‑0006896 leads to high expression of circRNA‑0006896 in ECs, which results in an increases in capacities of proliferation and migration in ECs.…”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%
“… 444 , 445 Wen et al suggested that the expression of exosomal circRNA‑0006896 in circulation is positively associated with the levels of TG, LDL, and C-reactive protein (CRP) in patients with unstable plaque atherosclerosis. 445 The study also reported that the elevated circulating exosomal circRNA‑0006896 leads to high expression of circRNA‑0006896 in ECs, which results in an increases in capacities of proliferation and migration in ECs. This effect is accompanied with the upregulation of DNMT1 and phosphorylation of STAT3, which may provide protection against the vulnerable plaque formation.…”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…We aimed to understand the role of circRNAs in serum exons of patients with stable plaque atherosclerosis (SA) and unstable/fragile plaque atherosclerosis (UA). Wen et al [ 26 ] studied the effect of circRNA on the behavior of human umbilical vein endothelial cells (HUVECs) and the mechanism of plaque instability in AS. They found significant differences in the expression profiles of circRNA in serum exons of SA and UA, indicating that circRNA may play a role in carotid plaque instability.…”
Section: Role Of Circrna In Ismentioning
confidence: 99%
“… 11 CircRNAs can regulate gene expression through multiple mechanisms, the most common of which is the large number of binding sites with sponging miRNAs, thus reducing the inhibitory effect of miRNA on target gene expression by competitively binding with miRNA. 12 Studies have shown that circRNAs play important roles in tumours, 13 cardiovascular diseases, 14 immune system diseases, etc. 15 , 16 However, the role of circRNAs in AGA is still unclear.…”
Section: Introductionmentioning
confidence: 99%